1992
DOI: 10.1007/bf02439326
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the surfactant (AOT) concentration in a reverse micellar extraction process

Abstract: SummaryThe surfactant concentration is an important parameter for optimizing protein extraction with microemulsions. Equilibrium and kinetic experiments show that the surfactant concentration can be reduced by a factor of 20 compared to published data. The masstransfer coefficient is found to be only about 18% lower for small AOT concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…At surfactant concentrations above 25 mM, solubilization increased only slightly. A similar protein solubilization-AOT concentration profile was achieved for the PT of CHY; however, the AOT concentration at which the protein solubilization plateau was reached was about 3 mM (Hentsch et al, 1992). Hentsch et al employed a much smaller w/o-ME/protein ratio than we employed here.…”
Section: Effect Of the Aot Concentrationmentioning
confidence: 64%
“…At surfactant concentrations above 25 mM, solubilization increased only slightly. A similar protein solubilization-AOT concentration profile was achieved for the PT of CHY; however, the AOT concentration at which the protein solubilization plateau was reached was about 3 mM (Hentsch et al, 1992). Hentsch et al employed a much smaller w/o-ME/protein ratio than we employed here.…”
Section: Effect Of the Aot Concentrationmentioning
confidence: 64%
“…In the forward extraction step, selection of sur-factants and pH play significant roles in protein stabilization. Sodium di-2-ethylhexyl sulfosuccinate (AOT) is the most common surfactant used in chymotrypsin purification [8][9][10][11]. pH influences ionic molecular interactions in solution and therefore, influences the efficiency of extraction by reverse micelles [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…This step is usually very slow and salt is added into the aqueous phase to assist the process [9]. However, increasing chloride ion concentration will decrease chymotrypsin yield by competing with chymotrypsin in the extraction process and the effect is particularly significant at low ionic strength [8,11]. According to Goto et al [12] and Hu and Gulari [9], the limitations of the backward extraction step are due to the difficulty in separating proteins from AOT reverse micellar phase and the excessive time involved in the process.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium di-2-ethylhexyl sulfosuccinate (AOT) is the most common surfactant used in chymotrypsin purification. It can form reverse micelles without adding co-surfactant (Jolivalt et al, 1990;Hu and Gulari, 1996;Hentsch et al, 1992). pH influences ionic molecular interactions in solution and, therefore, influences the efficiency of extraction by reverse micelles (Jolivalt et al, 1990).…”
Section: Reverse Micelles Methodmentioning
confidence: 99%
“…However, the pH of protein aqueous solutions should be held near a pH of 3 because at that pH the autohydrolysis rate is minimized and chymotrypsin is most stable (Hu and Gulari, 1996). Jolivalt et al (1990) and Hentsch et al (1992) reported that increasing chloride ion concentration will decrease chymotrypsin yield by competing with chymotrypsin in the extraction process and the effect is particularly significant at low ionic strength.…”
Section: Reverse Micelles Methodmentioning
confidence: 99%